Acute Oral Toxicity, Histopathological Analysis, and Antimalarial Potential of Jatropha tanjorensis Leaf Extracts - Fatima Jumare; Helen Ileigo Inabo; Muhammad Hassan Isa Doko; Gbonjubola Olusesan Adeshina (Asia Pacific Journal of Medical Toxicology)
Background: Jatropha tanjorensis is a leafy vegetable widely consumed across Africa and is valued in folk medicine for its reputed blood-replenishing properties. This study aimed to bridge this research gap by assessing the acute oral toxicity, histopathological effects on vital organs, and chemo-suppressive antimalarial activity of J. tanjorensis leaf extracts, offering crucial insights into their therapeutic potential and safety profiles.Methods: Different extracts of J. tanjorensis leaves were obtained by sequential extraction via maceration. Acute oral toxicity was assessed using the limit test at a dose of 5000 mg/kg body weight of the experimental mice, following the Organization for Economic Co-operation and Development (OECD) guidelines (425) for rats and mice. Histopathological analysis of the livers and kidneys of mice exposed to the extracts was performed using standard protocols. The chemo-suppressive antimalarial activity was determined using a suppressive test model. Data analysis was conducted using GraphPad Prism version 9.3.1.Results: The experimental mice exposed to J. tanjorensis leaf extracts exhibited no symptoms of toxicity, although one death was recorded across two groups. According to OECD guidelines, with fewer than three deaths observed, the LD50 of J. tanjorensis leaf extracts is estimated to exceed 5000 mg/kg body weight, indicating a high safety margin. Additionally, mice treated with the extracts showed slight weight gain, suggesting no adverse impact on overall health. Among the tested extracts, the ethyl acetate extract exhibited the highest chemo-suppressive antimalarial activity, achieving 80.7% inhibition of parasite growth in a dose-dependent manner, demonstrating its potential to suppress parasite proliferation during the early stages of infection.Conclusion: J. tanjorensis leaf extracts are promising candidates for further investigation as safe and effective antimalarial therapies, particularly for early-stage infections.